2010
DOI: 10.1128/cvi.00524-09
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Duration of Immunity Induced by Vaccination with a Canine Lyme Disease Bacterin

Abstract: Laboratory-reared beagles were vaccinated with a placebo or a bacterin comprised of Borrelia burgdorferi S-1-10 and ospA-negative/ospB-negative B. burgdorferi 50772 and challenged after 1 year with B. burgdorferiinfected Ixodes scapularis ticks. For the placebo recipients, spirochetes were recovered from 9 (60%) skin biopsy specimens collected after 1 month, and the organisms persisted in the skin thereafter. Ten (67%) dogs also developed joint infection (3 dogs), lameness or synovitis (7 dogs), or B. burgdorf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
2
24
1
Order By: Relevance
“…As an additional confounding factor, previous vaccination would further complicate diagnosis by an OspCbased antibody test because a widely used commercially available vaccine k prevents B. burgdorferi infection specifically by inducing high levels of anti-OspC antibodies against a widely conserved epitope. 3,4 In contrast, however, the results provided support for the previous observation 17 that dogs with Lyme disease more reliably produced anti-OspF antibodies, and that the response was associated most closely with later stages of the infection. In addition, we demonstrated that IgG antibodies predominated, and that the response was produced most often by dogs harboring spirochetes in the joints.…”
Section: Research-article2015contrasting
confidence: 56%
See 2 more Smart Citations
“…As an additional confounding factor, previous vaccination would further complicate diagnosis by an OspCbased antibody test because a widely used commercially available vaccine k prevents B. burgdorferi infection specifically by inducing high levels of anti-OspC antibodies against a widely conserved epitope. 3,4 In contrast, however, the results provided support for the previous observation 17 that dogs with Lyme disease more reliably produced anti-OspF antibodies, and that the response was associated most closely with later stages of the infection. In addition, we demonstrated that IgG antibodies predominated, and that the response was produced most often by dogs harboring spirochetes in the joints.…”
Section: Research-article2015contrasting
confidence: 56%
“…Archived serum samples from 24 healthy laboratory purpose-bred Beagles that had received only placebo prior to challenge with B. burgdorferi-infected ticks in previous studies 3,4 were then evaluated. The dogs were challenged by attaching 10 female and 10 male B. burgdorferi-infected I. scapularis ticks and allowing the female ticks to feed to repletion.…”
Section: Research-article2015mentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies (17,18) confirmed that the approach provided a high level of protection against canine Lyme disease for at least 1 year. In addition, the investigators demonstrated that the bacterin induced significant amounts of anti-OspC borreliacidal antibodies (17) and postulated that the high level of protection was likely due at least in part to the inclusion of the OspC-producing spirochete.…”
mentioning
confidence: 77%
“…All the dogs vaccinated with the vaccine containing OspC became positive as previously described with this vaccine. 1,9,10 6,9-11 protection may not be 100%, which emphasizes that vaccines against B. burgdorferi should not be used as the sole prevention strategy; it is imperative to also use acaricides as well. 12 The B. burgdorferi serological responses in the vaccinated dogs that developed infection were similar to those for dogs in experiment 2 that developed infection without being previously vaccinated.…”
Section: Discussionmentioning
confidence: 99%